2011
DOI: 10.1111/j.1365-2648.2011.05700.x
|View full text |Cite
|
Sign up to set email alerts
|

Medicine administration errors in patients with dysphagia in secondary care: a multi-centre observational study

Abstract: The increased medicine administration error rate in patients with dysphagia requires healthcare professionals to take extra care when prescribing, dispensing and administering medicines to this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 41 publications
3
99
0
3
Order By: Relevance
“…Twenty studies10 11 14 20–36 therefore met our inclusion criteria. Of these, four14 33 34 36 analysed data from previous studies;26 28 30 35 a final 16 unique studies were included. A third reviewer was not required.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies10 11 14 20–36 therefore met our inclusion criteria. Of these, four14 33 34 36 analysed data from previous studies;26 28 30 35 a final 16 unique studies were included. A third reviewer was not required.…”
Section: Resultsmentioning
confidence: 99%
“…However, in order to reduce the prevalence of ODF modifications, as observed in this and previous studies (Kelly et al, 2011b;Mercovich et al, 2014;Paradiso et al, 2002;Stubbs et al, 2008), it is important to firstly consider and address the key factors that give rise to ODF modification.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the cost of any deleterious consequences of inappropriate modifications must also be considered. In tandem with this, the potentially increased risk of medication errors also needs to be evaluated given the observation by Kelly et al (2011b) that patients with dysphagia experience a significantly higher risk of errors compared to patients without dysphagia. Further research is needed to assess the costeffectiveness of the various options.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised in the literature as to the merits of breaking down solid medications like this with the potential loss of substance, the influence this may have on therapeutic effect, the harm this may incur to nursing staff and the problems this may lead to with tube blockages [11,39]. To corroborate this, studies have shown that many errors occur during this process of solid drug breakdown, leading to potential harm to both patients and staff [40][41][42][43].…”
Section: Patient Issues and Procedural Complicationsmentioning
confidence: 99%